Chitosan/Polyvinyl Alcohol/Tea Tree Essential Oil Composite Films for Biomedical Applications - Jorge Iván Castro (MDPI AG, 2021)
Tissue engineering is crucial, since its early adoption focused on designing biocompatible materials that stimulate cell adhesion and proliferation. In this sense, scaffolds made of biocompatible and resistant materials became the researchers’ focus on biomedical applications. Humans have used essential oils for a long time to take advantage of their antifungal, insecticide, antibacterial, and antioxidant properties. However, the literature demonstrating the use of essential oils for stimulating biocompatibility in new scaffold designs is scarce. For that reason, this work describes the synthesis of four different film composites of chitosan/polyvinyl alcohol/tea tree (Melaleuca alternifolia), essential oil (CS/PVA/TTEO), and the subdermal implantations after 90 days in Wistar rats. According to the Young modulus, DSC, TGA, mechanical studies, and thermal studies, there was a reinforcement effect with the addition of TTEO. Morphology and energy-dispersive (EDX) analysis after the immersion in simulated body fluid (SBF) exhibited a light layer of calcium chloride and sodium chloride generated on the material’s surface, which is generally related to a bioactive material. Finally, the biocompatibility of the films was comparable with porcine collagen, showing better signs of resorption as the amount of TTEO was increased. These results indicate the potential application of the films in long-term biomedical needs.